CD155 density on target cells drives divergent Natural Killer cell responses owing to DNAM-1 loss - Saunders,PM; Oates,CVL; Hare,R; Burgess,M; Vargas,Pavia TA; Worboys,JD; Davis,MBE FMedSci D; Brooks,AG (Journal of Immunology, 2026)
Activation of natural killer (NK) cells by transformed targets requires the engagement of activating receptors and commonly a concomitant loss of inhibitory signaling. While the coactivating receptor DNAM-1 is involved in NK cell recognition of tumors expressing the nectin-like molecule CD155, in many cancer types, high expression of CD155 is associated with a poor clinical prognosis. To assess the impact of ligand density on NK cell function, recognition of target cells expressing low and high levels of CD155 was compared. While low levels of CD155 on target cells augmented NK cell activation, most evident in elevated IFN-γ responses, high levels of CD155 drove rapid, activation-induced downregulation of DNAM-1 that did not result in enhanced IFN-γ responses. High levels of CD155 also drove TIGIT loss from the NK cell surface; however, gene editing of TIGIT from primary NK cells had no significant impact on target cell recognition. Although low levels of CD155 induced a degree of DNAM-1 loss, the improved activation was still mediated through DNAM-1, as assessed through selective disruption of the interaction. Similarly, NK cell recognition of targets expressing the nectin CD112, which also engages both DNAM-1 and TIGIT, resulted in modest loss of DNAM-1 expression and heightened IFN-γ responses. Together, these observations suggest that DNAM-1 recognition of its ligands is delicately poised such that low avidity receptor engagement augments NK cell activation, and in particular IFN-γ responses, while stronger engagement can result in the rapid downregulation of DNAM-1 without any significant enhancement of effector responses.